Associations of physical activity and sedentary behaviour with metabolic syndrome in rural Australian adults. Issue 12 (December 2018) - Mitchell, Braden L.; Smith, Ashleigh E.; Rowlands, Alex V.; Parfitt, Gaynor; Dollman, James
Abstract: Objectives: Associations between objectively measured sedentary behaviour, physical activity (PA) and metabolic syndrome (MetS)-classified using three different definitions were investigated in an inactive sample of rural Australian adults. Design: Quantitative, cross-sectional. Methods: 171 adults (50.7 ± 12.4 years) from two rural South Australian regions underwent seven-day accelerometer activity monitoring and MetS classification using the National Cholesterol Education Program, the International Diabetes Federation and the Harmonized definitions. Associations between sedentary and activity variables and MetS (adjusted for age, sex, diet and smoking status) were modelled using logistic regression. In secondary modelling, associations of sedentary and activity outcomes for each MetS definition were assessed, adjusting for other activity and sedentary variables. Prediction differences across the definitions of MetS were directly compared using Akaike's Information Criterion. Results: Sedentary behaviour increased MetS risk, whereas light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA) reduced MetS risk, irrespective of definition. In secondary models, LPA predicted MetS independently of MVPA and total sedentary time. Time spent in sedentary bouts (>30 min) predicted MetS independently of MVPA and the number of sedentary bouts predicted MetS independently of LPA and MVPA. Prediction differences for MetS definitions failed to reach the critical threshold for difference (>10). Conclusions: This study highlights the importance of sedentary behaviour and LPA on the prevalence of MetS in an inactive sample of rural Australian adults. Studies assessing the efficacy of increasing LPA on MetS in this population are needed. Minimal predictive differences across the three MetS definitions suggest evidence from previous studies can be considered cumulative.